"Doctors Don't Kill Babies! Monsters Do!": using performance and personal narrative to identify the U.S. Abortion Monster. Issue 1 (2nd January 2022) - Ellis, Cassidy D.
ABSTRACT: This essay identifies a specific monster in U.S. American culture: the Abortion Monster. I demonstrate how abortion patients and providers are constructed as monstrous by anti-abortion rhetoric. I argue that anti-abortion rhetoric is not only about the decision to end or continue a pregnancy, rather it is a response to perceived deviation from performances of White heteropatriarchy. Abortion Monsters' rejection of hegemonic identity performances and/or their inability to embody such performances threatens and queerly reimagines heteronormative White supremacist norms. I demonstrate how performance scholarship is a space to explore the bodily imperatives and material implications of monstrosity in everyday life.